Serum TNF-α Level as a Possible Predictor of Inhibitor Levels in Severe Hemophilia A. (5th November 2021) - Susanah, Susi; Raspati, Harry; Sari, Nur Melani; Rakhmilla, Lulu Eva; Sribudiani, Yunia; Moestopo, Octawyana; Sinaga, Puspasari; Idjradinata, Ponpon; Maskoen, Ani Melani
Abstract : Background . The development of factor VIII (FVIII) inhibitor in patients with hemophilia A (PWHA) is a great challenge for hemophilia care. Both genetic and environmental factors led to complications in PWHA. The development of inhibitory antibodies is usually induced by the immune response. Tumor necrosis factor α (TNF- α ), one of the cytokines, might contribute to its polymorphism. In this study, we investigated the clinical factors, level of serum TNF- α, and polymorphism of c . − 308 G > A   TNF − α gene in inhibitor development in severe PWHA. Methods . A cross-sectional study was conducted among all PWHA in West Java province. The clinical parameters, FVIII, FVIII inhibitor, and serum TNF- α level were assessed. The genotyping of − 380 G > A TNF- α gene polymorphism was performed using polymerase chain reaction and Sanger sequencing. Results . Among the 258 PWHA, 216 (83.7%) were identified as severe PWHA. The FVIII inhibitor was identified in 90/216 (41.6%) of severe PWHA, consisting of 45 high-titer inhibitors (HTI) and 45 low-titer inhibitors (LTI). There was a significant correlation between serum TNF- α level and the development of HTI (p = 0.043 ). The cutoff point of serum TNF- α level, which can be used to differentiate between HTI and LTI, was 11.45 pg/mL. The frequency of FVIII replacement therapy was significant only in HTI of severe PWHA regarding serum TNF- α level (p = 0.028 ). There is no correlation between polymorphisms of − 380 G > A TNF- α gene and inhibitor development (p = 0.645 ). Conclusions . The prevalence of FVIII inhibitor in severe PWHA in West Java, Indonesia, was 41.6%. The frequency of replacement therapy is a risk factor for inhibitor development. Serum TNF- α level might be used to differentiate between high and low inhibitor levels in severe hemophilia A, and this might support decision making regarding treatment options for inhibitor in severe hemophilia A.